Cytogenetic Studies of 608 couples with Recurrent Spontaneous Abortions in Northeastern Iran - Narjes Soltani; Farzaneh Mirzaei; Hossein Ayatollahi (Iranian Society of Pathology, 2021)
Background & Objective: One of the major genetic causes of recurrent spontaneous abortions is parental chromosomal abnormalities. The objectives of the study were to determine, compare and analyze the incidence and distribution of chromosomal abnormalities in couples with recurrent miscarriages from Northeastern Iran.Methods: This study was conducted at Ghaem Hospital, Mashhad, Iran. We evaluated karyotype results of 608 couples with history of recurrent spontaneous abortion. The standard method was used for culturing peripheral venous blood lymphocytes.Results: Chromosome aberrations were detected in 43 patients (3.54%), including 25 females and 18 males. Structural chromosomal abnormality was detected in 40 cases, including balanced translocations (25 cases), robertsonian translocations (4 cases), inversions (10 cases) and numerical chromosome aberrations (3 cases). Polymorphic variants were observed in 22 individuals.Conclusion: The frequency of chromosomal abnormalities in couples with Recurrent Spontaneous Abortion (RSA) in our study is 3.54%. Reciprocal translocation, pericentric inversions, robertsonian translocations, and numerical abnormality observed among couples who had experienced recurrent spontaneous abortions and that these couples might benefit from cytogenetic analysis.